High-yield cultivation of Botryococcus braunii for biomass and hydrocarbons. (December 2019) - Wan, Minxi; Zhang, Zhen; Wang, Ruixuan; Bai, Wenmin; Huang, Jianke; Wang, Weiliang; Shen, Guomin; Yu, Anquan; Li, Yuanguang
Abstract: Botryococcus braunii is one of the most promising energy microalgae with a high content of hydrocarbons. Photoautotrophic cultivation is essential while the productivity is lowered by the long period of preparation for seeds. Therefore, a new strategy of photoautotrophic culture with heterotrophic seeds was proposed. The pH-auxostat fed-batch heterotrophic cultivation was developed, by which the biomass reached 37.02 g L −1 at 28 day in the 5 L fermenter. The effects of inoculum with heterotrophic seeds into photoautotrophic cultivation were verified. By this strategy, the final content and productivity of hydrocarbon was 35.9% and 128.3 mg L −1 d −1 respectively in 1 L bubble column photo-bioreactors indoors, the highest ever reported. Furthermore, the heterotrophic seeds were successfully applied to photoautotrophic cultivation in 3 L flat panel photo-bioreactors and 120 L open circle ponds outdoors, in which the final content and productivity of hydrocarbon were 27.85% and 35.06 mg L −1 d −1, indicating an efficient and feasible approach for producing biofuel from B. braunii . Graphical abstract: Image 1 Highlights: The HS-PC method has been established successfully to grow Botryococcus. DCW of 37 g L −1 was obtained using heterotrophy in 5L fermenter. The hydrocarbon content had reached 35.9% using HS-PC. The productivity of hydrocarbon was up to 12.2 mg L −1 d −1 using HS-PC.